MEMAHAMI HADIS MISOGINIS DALAM PERSPEKTIF HERMENEUTIKA PRODUKTIF HANS GADAMER - Mohammad Muhtador (UIN Siber Syekh Nurjati Cirebon, 2018)
This paper examines misogynistic hadith by using hermeneutical Hans Gadamer. The spread of misogynistic hadith in Islamic literature has had a negative impact on the existence of women in private and public areas, where the traditions are understood in textual-patrial ways that benefit men. In this region, new readings are needed to explore the meaning of humanity as Prophet Muhammad was sent for moral change. The hermeneutic theory is used to find hidden values behind the text and understanding. This study is a literature study that explores data from the literature to find a picture in reading misogynistic hadiths. So that it can be concluded that hermeneutics is used to break the gap in understanding misogynistic hadith, misogynistic hadith is the result of the Prophet's interaction with the context in his time and misogynistic hadith is still open to interpreted various approaches and theories that allow finding the moral values contained in it.